Interlimb coordination : neural, dynamical, and cognitive constraints - Swinnen, S. P. (Stephan P.) (Academic Press, 1994)
This comprehensive edited treatise discusses the neurological, physiological, and cognitive aspects of interlimb coordination. It is unique in promoting a multidisciplinary perspective through introductory chapter contributions from experts in the neurosciences, experimental and developmental psychology, and kinesiology. Beginning with chapters defining the neural basis of interlimb coordination in animals, the book progresses toward an understanding of human locomotor control and coordination and the underlying brain structures and nerves that make such control possible. Section two focuses on the dynamics of interlimb coordination and the physics of movement. The final section presents information on how practice and experience affect coordination, including general skill acquisition, learning to walk, and the process involved in rhythmic tapping.